WAR AND CONFLICT STUDIES - Afonso, Henrique Weil (Revista Ética e Filosofia Política, 2018)
International community is witnessing the dawn of new era where the traditional conception of war is being questioned as new threats to international security rise. Such menaces are materialized as the war against terrorism, wars of national liberation and domestic ‘wars’ and the need for humanitarian intervention. Regardless of the significance of “new wars”, International Law war-related legislation insists on turning a blind eye to the evolution of warfare and the emergence of contemporary peril brought about by some states to their own populations. Therefore, it could be argued that humanitarian intervention consists of a legitimate cause for engaging in war.